Factors affecting sleep disturbances among hospitalized geriatric patients in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan - Rosli, Awatif Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Complaints of an inability to sleep are common occurrences during hospitalization of elderly people and often left unmanaged. The aim of this descriptive study is to determine the factors affecting sleep disturbances among geriatric patients during hospitalization in Hospital Universiti Sains Malaysia. A purposive sample of 100 geriatric patients who were admitted to the selected surgical and medical ward were included in this study. Data was collected through a modified questionnaire combination from past study literatures done by using SPSS software 20.0. Based on descriptive analysis, the prevalence of sleep Chi-Square Test was used to test the relationship between environmental factors, psychological factors and physiological factor with sleep disturbances. Apart from that, the test also was used to study the relationship between sleep disturbances and degree of daytime sleepiness. The results shows that there is a significant relationship between environmental factor of noise and sleep disturbances with p = 0.031. Two sources of with p = 0.027 and p = 0.021 respectively. Findings from the study show a significant relationship between sleep disturbances and degree of daytime sleepiness with p - 0.006. In conclusion, once the contributing factors known, appropriate interventions could be implemented to minimize the occurrences.